A Practical Approach to Excessive Daytime Sleepiness: A Focused Review - Brian J. Murray (Canadian Respiratory Journal)
Excessive daytime sleepiness (EDS) is a common problem that is important to recognize and address. Initial steps in management are generally straightforward and only the most advanced cases would require referral to a subspecialist. Of particular concern is that of driving safety. There is a broad differential diagnosis for conditions contributing to EDS but a few common conditions account for the majority of clinical presentations. Subjective self-reporting will often lead to identification of potential problems, but this is often unreliable. Traditional neurophysiologic tests can help in objectively quantifying symptoms but current tests are not always practical clinically and may have little validation in real world situations. There are many treatment options that should generally be able to sufficiently manage most patients presenting with hypersomnolence. This review provides a practical clinical approach to the problem based on current guidelines.